Ultracool dwarf benchmarks with Gaia primaries - Marocco, Federico; Pinfield, David J.; Caballero, José A. (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. We explore the potential of Gaia for the field of benchmark ultracool/brown dwarf companions, and present the results of an initial search for metal-